On control of chaos in the Kerr lens mode locked Ti:Sapphire laser - Kovalsky, Marcelo Gregorio (2006)
In this paper, I present the numerical demonstration of a simple way to reduce the pulse duration of a Kerr lens mode locked Ti:Sapphire laser. The core of the method lies in the low dimensional deterministic chaos that displays the laser. By adding an acousto optic modulator and applying an adequate control algorithm, it is possible to reduce the pulse duration by a factor of two with a laser that otherwise operates in the range of 40 fs.